JUMP‐C: A randomized trial of mericitabine plus pegylated interferon alpha‐2a/ribavirin for 24 weeks in treatment‐naïve HCV genotype 1/4 patients. Issue 2 (24th June 2013) - Pockros, Paul J.; Jensen, Donald; Tsai, Naoky; Taylor, Ryan; Ramji, Alnoor; Cooper, Curtis; Dickson, Rolland; Tice, Alan; Kulkarni, Rohit; Vierling, John M.; Lou Munson, Marie; Chen, Ya‐Chi; et al.
<x xml:space="preserve">Abstract</x> Mericitabine is a selective nucleoside analog inhibitor of the hepatitis C virus (HCV) NS5B RNA‐dependent RNA polymerase, with activity across all HCV genotypes. Treatment‐naïve patients infected with HCV genotype 1 or 4 were randomized to 24 weeks of double‐blind treatment with either mericitabine 1, 000 mg (N = 81) or placebo (N = 85) twice‐daily (BID) in combination with pegylated interferon alpha‐2a (Peg‐IFNα‐2a)/ribavirin (RBV). Patients randomized to mericitabine with HCV RNA <15 IU/mL from week 4 to 22 (extended rapid virologic response; eRVR) stopped all treatment at week 24; all other patients continued Peg‐IFNα‐2a/RBV to complete 48 weeks of treatment. The primary efficacy endpoint was sustained virologic response (SVR; HCV RNA <15 IU/mL after 24 weeks of treatment‐free follow‐up). SVR was achieved in 56.8% (95% confidence interval [CI]: 45.9‐67.0) of mericitabine‐treated patients and 36.5% (95% CI: 27.0‐47.1) of placebo‐treated patients (Δ = 20.3%; 95% CI 5.5‐35.2). SVR rates were higher in mericitabine‐ than placebo‐treated patients when subdivided by IL28B genotype (CC, 77.8% versus 56.0%; non‐CC, 44.1% versus 16.2%) and hepatic fibrosis (noncirrhotic, 63.3% versus 41.9%; cirrhotic, 38.1% versus 21.7%). Overall relapse rates were 27.7% and 32.0% in mericitabine‐ and placebo‐treated patients, respectively. No evidence of NS5B S282T‐variant virus or phenotypic resistance to mericitabine was observed in the one patient who experienced partial response. No S282T variants were detected in any baseline samples. The safety profile of mericitabine was similar to that of, and fewer patients in the mericitabine than in the placebo group discontinued treatment for safety reasons. Conclusion: A 24‐week response‐guided combination regimen of mericitabine 1, 000 mg BID plus Peg‐IFNα‐2a/RBV is well tolerated and more effective than a standard 48‐week course of Peg‐IFNα‐2a/RBV. (HEPATOLOGY 2013;58:514–523)